Effectiveness of primary vaccination against tick-borne encephalitis in employees of the armed forces - Dorko, Erik; Bušová, Andrea; Rimárová, Kvetoslava; Drabiščák, Erik; Kizek, Peter; Popaďák, Peter; Popaďáková, Jana; Jenčová, Janka; Jenča, Andrej; Petrášová, Adriána (Central European journal of public health, 2018)
OBJECTIVE: The aim of our study is to evaluate immune response after receiving the primary vaccination against tick-borne encephalitis (TBE), and to establish a link between seropositivity and selected factors in soldiers. METHODS: Blood samples, questionnaires and vaccination records were obtained. TBE antibodies were detected using both ELISA and a neutralization test (NT). We used logistic regression for statistical analysis. RESULTS: Overall, seropositivity (presence of IgG) was detected in 88% of participants. The proportion of seropositive subjects in relation to the number of doses of vaccine was 69% (2 doses) and 91% (3 doses). A statistically significant relationship was found between seropositivity and the number of vaccine doses. No statistical significance was identified in relation to age and sex. There was no statistical significance of seropositivity, depending on the time of the last dose of the vaccine. CONCLUSIONS: TBE immunisation should be targeted at individuals in the most affected locations and those at highest risk of exposure according to lifestyle and occupation.
Keywords: Vaccination; Viral Vaccines; neutralizační testy; Adult; Male; viry klíšťové encefalitidy; imunoglobulin G; Encephalitis, Tick-Borne; lidé; ELISA; lidé středního věku; Humans; Encephalitis Viruses, Tick-Borne; soldiers; Middle Aged; Neutralization Tests; tick-borne encephalitis; immune response; Enzyme-Linked Immunosorbent Assay; Military Personnel; klíšťová encefalitida; protilátky virové; vaccination; ozbrojené síly; mužské pohlaví; Antibodies, Viral; Immunoglobulin G; dospělí; virové vakcíny; ženské pohlaví; Female; vakcinace